Becoming a project beneficiary in a mining region: Work, Negotiations and Development Programs in Northern Peru - Adriana Paola Paredes Peñafiel; Guilherme Francisco Waterloo Radomsky (Vibrant: Virtual Brazilian Anthropology)
Abstract: In the northern Peruvian Andes, a large mining project assumes unique characteristics when a single company becomes an agent of development and accountability programs, contracts the workers and promotes local entrepreneurship. Based on ethnographic field research conducted between 2013 and 2014, this article explores the relationship between the mining company and the population of Hualgayoc, in the Cajamarca region. Mining enterprises generate all kinds of desires in people, including getting a job or financial compensation for land sales. Once the mine is constructed, direct employment becomes rare and environmental problems appear, development programs thus emerge as strategic actions, offering scenarios for conflicts and negotiations. While the company occupies a delicate boundary between assuming a state-like role or merely encouraging self-sufficiency in the local economy, the population seek to perpetuate ties with the corporation. Consequently, becoming a beneficiary of a project or compensation may represent one of the few available options.